Trans-dimensional Bayesian electromagnetic inversion for geothermal reservoir characterization in South China: Uncertainty analysis of subsurface conductivity recovered from CSAMT data - Shengqi Tian; Peng Xue; Rongwen Guo; Jianxin Liu; Keke Zhou; Yongfei Wang; Jihai Mo; Jianjian Li; Heming Su (Geothermics, 2026)

Cu-N3C single-atom sites activated peroxymonosulfate for electron transfer pathway toward stable and efficient removal of triazine contaminants - Xiaopeng Huang; Yabin Li; Qingong Song; Heming Luo; Linhai Yang; Xiaolong Tang; Xia Zhao; Zhe Wang; Jianghe Chen; Jianhua Hou; Shenglong Hu (Chemical Engineering Journal, 2026)

An integrated source–exposure–transport framework for risk-oriented management of mining-impacted groundwater contamination - Chang Liu; Yimin Sang; Fan Feng; Tingyu Yang; Qingyue Wang; Yanwei Wang; Heming Wang; Fujun Ma; Qingbao Gu (Journal of Environmental Chemical Engineering, 2026)

Characteristics and source apportionment of VOCs and their contribution to ozone formation in a typical chemical industrial park - Yuxin Jia; Qiang Yue; Heming Wang (Atmospheric Environment, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Co-removal of norfloxacin and Cr(VI) by Co/N-doped carbon activating peroxymonosulfate: 1O2 oxidation coupled with interfacial electron transfer - Yaru Li; Heming Wang; Rong Qiao; Dongxu Zhou; Fuyun Deng; Gaoyang Chen; Peixin Mao; Chaolin Yang; Xiaodong Zhang (Environmental Research, 2026)

Criticality and scale effects in China's power lithium-ion battery system - Yue Zhang; Yao Wang; Fengmei Ma; Asaf Tzachor; Heming Wang (Journal of Environmental Management, 2026)

Canopy gap disturbance restructures growth-mortality trade-offs of dominant canopy species in the understory - Shiwei Yu; Xuyang Zhu; Huimin Yin; Qingsong Yang; Shan Jiang; Qiuwu Yu; Xiwen Zheng; Jianan Wang; Heming Liu; Xihua Wang (Forest Ecology and Management, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Tracking the carbon footprint of the iron and steel industry along the supply chain: From the urban agglomeration level - Huanyu Wang; Qiang Yue; Zhenyu Cheng; Yuqi Lu; Yujie Zhang; Heming Wang; Tao Du; Yisong Wang (Journal of Cleaner Production, 2026)

The colonization, succession and ecological processes of saxicolous moss crust in the Qinling Mountains - Chun Wang; Jin Fan; Heming Wang; Qiuxia Mo; Xiangzhou Chen; Wenjuan Zhou; Chongfeng Bu; Yongsheng Xie (CATENA, 2026)

Engineering strategies for the biosynthesis of rare sugars in microbial cell factories - Heming Xu; Ran Lu; Mei-Li Sun; Lu Lin; Kaifeng Wang; Xiao-Jun Ji (World Journal of Microbiology and Biotechnology, 2026)

Toward a standardized and comparable life cycle dataset system for steel production in China - Huanyu Wang; Qiang Yue; Huimin Chang; Xiang Fu; Wei Ji; Changqing Xu; Heming Wang (Resources, Conservation and Recycling, 2026)

Network-driven prioritization of high-impact sectors for the low-carbon transportation system - Wenju Sun; Yao Wang; Qiang Yue; Yisong Wang; Wenqiang Sun; Tao Du; Heming Wang (Journal of Cleaner Production, 2026)

The Mechanical Microenvironment of Trabecular Bones Subjected to a Physiological Gait Load - Yan Wang; Heming Chen; Baopeng Wu; Zhiyong Li; Nicola M. Pugno; Xiaogang Wu; Qiang Chen (Annals of Biomedical Engineering, 2026)

Enhancing the catalytic performance of ZnZrOx/SAPO-34 bifunctional catalysts through structural modulation - Rui Xiang; Tao Du; He Jia; Yingnan Li; Peng Chen; Qiang Yue; Heming Wang; Yisong Wang (Journal of Environmental Chemical Engineering, 2026)

Model-Dependent Attenuation of Seizures by Cinnabar - Yuang Gu; Yu Yao; Qiuwen Lou; Xinyan Zhu; Ju Lan; Chenshu Gao; Shuangshuang Wu; Jingjia Liang; Cenglin Xu; Yi Wang; Heming Cheng; Zhong Chen (Neuroscience Bulletin, 2026)

High-performance polyurethane urea for sealing applications in extreme temperature conditions - Kai Zhou; Jianfeng Xie; Hangyu Shen; Junhui Gong; Xianqiang Pei; Xinrui Zhang; Heming Luo; Yong Yang; Qihua Wang; Yaoming Zhang (Chemical Engineering Journal, 2026)

Acute Stress Facilitates Cognitive Control in Healthy Men: an fNIRS Study - Xiaoman Wang; Heming Gao; Mingming Qi (Brain Topography, 2026)

Stability of β-cyclodextrin interface-modified iron-carbon composite and its migration in porous media - Kangping Huang; Tianwen Zheng; Xinyue Li; Ziyin Yang; Ruoxi Li; Yizhou Liu; Naijin Wu; Moxi Wang; Liqin Zhi; Huilong Luo; Wenxia Wei; Peizhong Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Impact of steam explosion on Sorghum starch digestibility and physicochemical properties - Xiaoli Ma; Heming Wang; Yuan Zhang; Peiyan Li; Danyang Li; Kun Yu (Food Research International, 2025)

Long-term removal characterization of trichloroethylene from groundwater using sustained-release iron-carbon composite: Investigations through batch and column experiments - Kangping Huang; Tianwen Zheng; Xinyue Li; Ziyin Yang; Ruoxi Li; Yizhou Liu; Wenxia Wei; Yimin Sang; Heming Wang (Environmental Research, 2025)

Molecular insights into the adsorption behavior of PFAS on montmorillonite, polyethylene, and polypropylene: A molecular dynamics study - Qiao Wang; Rui Xu; Fusheng Zha; Long Xu; Bo Kang; Heming Han (Computers and Geotechnics, 2025)

Elastic-wave reflection “bright spot” of a fractured rock formation: Theoretical analysis and deep-well acoustic imaging evidence - Xiaoming Tang; Wenhao Wang; Heming Wang; Kaiyin Zheng (Science China Earth Sciences, 2025)

Internal electric field and atomic-level interface modulation of V-MoS2/ZnIn2S4 heterojunction for efficient photocatalytic Uranium(VI) removal - Zhijian Zheng; Zifang Ye; Haiwei Qiu; Hongyi Wang; Xizao Wang; Heming Zhu; Zhian Wang; Youqun Wang; Zhimin Dong; Zhibin Zhang; Yibao Liu; Yunhai Liu (Journal of Environmental Chemical Engineering, 2025)

An efficient polysilicate aluminum ferric (PSAF) for drilling wastewater treatment: Performance evaluation and coagulation mechanisms - Huihui Zhang; Qiang Li; Futang Hu; Changkun Cheng; Nan Su; Zhiyong Zhang; Zhongzhi Zhang; Yijing Luo; Heming Wang (Journal of Environmental Chemical Engineering, 2025)

Predicting the flavor potential of green coffee beans with machine learning-assisted visible/near-infrared hyperspectral imaging (Vis-NIR HSI): Batch effect removal and few-shot learning framework - Minping Wu; Zhuangwei Shi; Haiyu Zhang; Rui Wang; Jiayi Chu; Shao Quan Liu; Heming Zhang; Hai Bi; Weihua Huang; Rui Zhou; Chenhui Wang (Food Control, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

The effectiveness of Go/Nogo dual-task is modulated by SOA and Go/Nogo ratio - Xiaoman Wang; Guiqin Ren; Heming Gao; Mingming Qi (Behavioural Processes, 2025)

Effect of static magnetic field-assisted repeated freezing and thawing on quality characteristics, microstructure, and myofibrillar protein properties of lamb meat - Jinxiao Liu; Wang Heming; Pengfei Du; Weiting Wang; Yaobo Liu; Guoyuan Xiong; Kun Yu; Yanli Ma (Innovative Food Science & Emerging Technologies, 2025)

Abundant taxa enhanced stability of fungal communities according to reduced nitrogen fertilization - Heming Han; Bo Zhang; Hao Liu; Yue Li; Xu Weidong; Liting Zhang; Hui Cao; Feng Wang (Soil and Tillage Research, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Energy savings and emission reduction benefits of China's aluminum use paths in transport sector - Xinpeng Zheng; Qiang Yue; Heming Wang (Science of The Total Environment, 2025)

In situ synthesis of MIL-101 on carboxyl-functionalized SBA-16: Preparation and catalytic performance in the Knoevenagel condensation reaction under mild conditions - Chunlai Liu; Na Wang; Zelin Meng; Mingyang Song; Heming Zhao; Jianglei Hu; Fengwei Shi (Journal of Environmental Chemical Engineering, 2025)

Rapid identification of defects in doped organic crystalline films via machine learning-enhanced hyperspectral imaging - Lijiao Wu; Wei Wang; Zhuangwei Shi; Haiyu Zhang; Lianbao Ke; Xiaohong Liang; Detian Tian; Heming Zhang; Hai Bi; Wangqiao Chen; Guofu Zhou (Chemical Engineering Journal, 2025)

Effects of Grass Cultivation on the Soil Organic Carbon of Citrus Orchard Soil and Their Microbial Mechanisms in Red Soil Hilly Areas - Zhuopin Zhuo; Heming Li; Bangning Zhou; Xiaopeng Wang; Xiaohui Lin; Lei Wang; Fangshi Jiang; Jinshi Lin; Yanhe Huang; Yue Zhang (Journal of Soil Science and Plant Nutrition, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

A decade of ecological and environmental research on the belt and road initiative: Evolution and future directions - Yongyue Gong; Heming Wang; Asaf Tzachor; Tomer Fishman; Fengmei Ma; Lingli Hou; Yao Wang; Wenju Sun; Yihan Song; Kai Fang; Wei-Qiang Chen; Yuri Mazei; et al. (Resources, Conservation and Recycling, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Silicon-related materials demand and embodied greenhouse gas emissions of photovoltaic systems in China's regions - Xiaozhu Xu; Xing Chen; Heming Wang; Lianzheng Zhao; Zhi Wang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2025)

Material flows and embodied carbon emissions of aluminum used in China's photovoltaic industry from 2000 to 2020 - Yongsheng Lei; Xiaozhu Xu; JingZhong Li; Heming Wang; Qiang Yue; Wei-Qiang Chen (Resources, Conservation and Recycling, 2025)

The evolution of research at the intersection of industrial ecology and artificial intelligence - Yongyue Gong; Fengmei Ma; Heming Wang; Asaf Tzachor; Wenju Sun; Junming Zhu; Gang Liu; Heinz Schandl (Journal of Industrial Ecology, 2025)
The intersection of artificial intelligence (AI) and industrial ecology (IE) is gaining significant attention due to AI's potential to enhance the sustainability of production and consumption systems. Understanding the current state of research in this field can highlight covered topics, identify trends, and reveal understudied topics warranting future research. However, few studies have systematically reviewed this intersection. In this study, we analyze 1068 publications within the IE–AI domain using trend factor analysis, word2vec modeling, and top2vec modeling. These methods uncover patterns of topic interconnections and evolutionary trends. Our results identify 71 trending terms within the selected publications, 69 of which, such as “deep learning,” have emerged in the past 8 years. The word2vec analysis shows that the application of various AI techniques is increasingly integrated into life cycle assessment and the circular economy. The top2vec analysis suggests that employing AI to predict and optimize indicators related to products, waste, processes, and their environmental impacts is an emerging trend. Lastly, we propose that fine‐tuning large language models to better understand and process data specific to IE, along with deploying real‐time data collection technologies such as sensors, computer vision, and robotics, could effectively address the challenges of data‐driven decision‐making in this domain.

Revealing global supply risk of critical minerals essential for low-carbon energy technologies - Xinran Xing; Yawei Huang; Yao Wang; Heming Wang; Peng Wang; Tao Dai; Gang Liu; Asaf Tzachor (Journal of Cleaner Production, 2025)

Investigation of instability characteristics and lean-burn limit of methane/air laminar premixed flames at sub-atmospheric pressure - Xiao Yang; Jianmin Gao; Hao Wang; Min Xie; Qian Du; Yu Zhang; Dongdong Feng; Heming Dong; Ziqi Zhao (Fuel, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

Assessing the environmental impacts associated with China's battery minerals and technologies - Yawei Huang; Heming Wang; Asaf Tzachor (Resources, Conservation and Recycling, 2025)

Bridging environmentally extended input-output models and complex network analysis: A bibliometric analysis of trends and opportunities - Wenju Sun; Fengmei Ma; Asaf Tzachor; Yao Wang; Yongyue Gong; Chao Wang; Xiaoqian Hu; Heming Wang (Journal of Cleaner Production, 2025)

Hybrid multi-stage steel footprinting unveils a more interdependent material foundation of the global economy - Xinyi Li; Chao Zhang; Xue Yang; Ziqian Xia; Zhi Cao; Peng Wang; Heming Wang; Tao Wang; Gang Liu; Wei-Qiang Chen (Ecological Economics, 2025)

Global material flows and resource productivity: The 2024 update - Heinz Schandl; Raymundo Marcos‐Martinez; James West; Alessio Miatto; Stephan Lutter; Mirko Lieber; Stefan Giljum; Manfred Lenzen; Mengyu Li; Heming Wang; Hiroki Tanikawa; Fridolin Krausmann; et al. (Journal of Industrial Ecology, 2024)
Accurate assessments of global primary material extraction, trade of primary materials and products, material use, waste, and emissions support the development of policies that facilitate the decoupling of economic activity, natural resource use, and related environmental impacts. Here, we quantify all crucial aspects of global and country‐by‐country material requirements needed to fuel economic activities, covering both territorial‐ and demand‐based indicators. These data have been assembled by a consortium of research partners that compile the global material flow and resource productivity online database for the International Resource Panel, which contributes to the global dataset for the System of Environmental–Economic Accounting (SEEA) framework and is employed to monitor progress for the Sustainable Development Goal (SDG) indicators 8.4 and 12.2. We present the main findings of the 2024 update, including methodological improvements and result differences, and discuss the main findings and limitations. Since the last update, we have identified a slowing of global materials extraction since about 2014, a continuation of solid growth in direct trade of materials and products, persistent inequality in resource use between high‐ and low‐income countries, and a prolonged improvement in global material productivity. The full dataset used herein can be downloaded from the Global Material Flow Database hosted by the United Nations Environment Program International Resource Panel.

Scenario analysis of waste tires from China's vehicles future - Di Cui; Zihan Bi; Yao Wang; Yilu Gu; Heming Wang; Xiaofeng Gao; Peng Wang; Xin Sun; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Material demand and recycling potential driven by wind power expansion in China - Zhi Wang; Congliang Hu; Heming Wang; Tao Dai; Xiaozhu Xu; Litao Liu (Journal of Environmental Management, 2024)

Highly efficient catalytic hydrogenation of nitrobenzene on cobalt- immobilized nitrogen-doped carbon: A dual-sites synergistic effect between cobalt single atoms and cobalt nanoparticles - Heming Qi; Xingling Wang; Ming Lei; Wenyu Fan; Shuangshuang Huang; Lihua Zhu; Heqing Tang (Chemical Engineering Journal, 2024)

Regional water-energy-carbon footprint in the context of sustainable development based on EE-MRIO: cases of Jiangsu, Zhejiang and Shanghai - Huanyu Wang; Qiang Yue; Rui Liu; Yujie Zhang; Heming Wang; Qi Wang (Environment, Development and Sustainability, 2024)

Bimetallic NiCu catalyst derived from spent MOF adsorbent for efficient photocatalytic CO2 reduction - Longyun Zhang; Ganghua Zhou; Gaoran Chen; Heming Wang; Qian Zhao; Weiqin Yin; Jianjian Yi; Xingwang Zhu; Xiaozhi Wang; Xin Ning (Chemical Engineering Journal, 2024)

Research on copper flow and environmental load in China's new infrastructure industry for carbon neutrality - Yuqi Lu; Guangxin Liu; Qiang Yue; Yingjie Fu; Heming Wang; Zhihe Dou; Yisong Wang; Tao Du (Journal of Cleaner Production, 2024)

Preparation of catalyst for CO2 hydrogenation reaction based on the idea of element sharing and preliminary exploration of catalytic mechanism - He Jia; Tao Du; Yingnan Li; Heming Wang; Qiang Yue; Lifeng Zhou; Yisong Wang (Environmental Science and Pollution Research, 2024)

A simple projection method to correlate the principal mechanical direction with the principal microstructural direction of human osteoporotic femoral heads - Heming Chen; Dong Wang; Jiayi Li; Qingqiang Yao; Nicola M. Pugno; Zhiyong Li; Qiang Chen (Medical & Biological Engineering & Computing, 2024)

2D/1D nested hollow porous ZnIn2S4/g-C3N4 heterojunction based on morphology modulation for photocatalytic CO2 reduction - Ziang Zheng; Tao Du; Peng Chen; Qiang Yue; Heming Wang; Lifeng Zhou; Yisong Wang (Journal of Environmental Chemical Engineering, 2024)

China's pathway towards a net zero and circular economy: A model-based scenario analysis - Yingying Lu; Heinz Schandl; Heming Wang; Junming Zhu (Resources, Conservation and Recycling, 2024)

The influence of simulated weightlessness on the composition and function of gut microbiota and bile acid metabolism products - Min Wang; Sheng Chen; Changqing Zhong; Lei Liu; Guodong Wang; Xin Huang; Xiaoman Yang; Heming Yang; Lianyong Li (Life Sciences in Space Research, 2024)

Assessing the supply risks of critical metals in China's low-carbon energy transition - Pengfei Yuan; Dan Li; Kuishuang Feng; Heming Wang; Peng Wang; Jiashuo Li (Global Environmental Change, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Multinational dynamic steel cycle analysis reveals sequential decoupling between material use and economic growth - Xue Yang; Chao Zhang; Xinyi Li; Zhi Cao; Peng Wang; Heming Wang; Gang Liu; Ziqian Xia; Dajian Zhu; Wei-Qiang Chen (Ecological Economics, 2024)

A self-adaptive parallel image stitching algorithm for unmanned aerial vehicles in edge computing environments - Xin Xu; Li Zhang; Jibo Yue; Heming Zhong; Ying Wang; Jie Liu; Yanhui Lu; Hongbo Qiao (International Journal of Remote Sensing, 2024)

Impact of spatial scales of control measures on the effectiveness of ozone pollution mitigation in eastern China - Rusha Yan; Hongli Wang; Cheng Huang; Jingyu An; Heming Bai; Qian Wang; Yaqin Gao; Shengao Jing; Yanyu Wang; Hang Su (Science of The Total Environment, 2024)

Green steel: The future path towards sustainable automotive manufacturing - ShangHeng Yao; Haojun Zhu; Si Zhang; Huimin Chang; Heming Wang (Resources, Conservation and Recycling, 2024)

Biomimetic metal organic frameworks mediated by metformin and 1-MT for enhancing the synergistic treatment of photodynamic therapy, photothermal therapy and immunotherapy - Zhihao Bai; LianShan Guo; JianFeng Huang; HaoYu Li; Guanghui An; Heming Zheng; Nannan Wang; Zhengzhao Li; Yanqiu Zhu (Chemical Engineering Journal, 2024)

Technology transition strategies for textile-dyeing sludge management in China from the environmental and economic perspectives - Yongyue Gong; Fang Liu; Hanqiao Liu; Heming Wang; Yuxuan Zhao; Yanfei Lin (Sustainable Production and Consumption, 2023)

Critical minerals for sustainability: More haste, less speed - Yao Wang; Asaf Tzachor; Heming Wang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2023)

Quantifying economic sectoral iron commodity use and related vulnerability in China's supply chains - Yao Wang; Fengmei Ma; Asaf Tzachor; Peng Wang; Heming Wang; Jie Lyu; Qiang Yue; Tao Du; Wei-Qiang Chen; Sai Liang (Resources, Conservation and Recycling, 2023)

Techno-economic assessment and exergy analysis of iron and steel plant coupled MEA-CO2 capture process - Yuhang Yang; Tao Du; Yingnan Li; Qiang Yue; Heming Wang; Liying Liu; Shuai Che; Yisong Wang (Journal of Cleaner Production, 2023)

An EGCG-mediated self-assembled micellar complex acts as a bioactive drug carrier - Chao Liu; Hao Wu; Hongxia Duan; Yan Hou; Shuangqing Wang; Yanhong Liu; Xintong Zhang; Heming Zhao; Liming Gong; Hongshuang Wan; Bowen Zeng; Xiuquan Quan; et al. (Food Chemistry, 2023)

Numerical study of aerodynamic performance of horizontal axis dual-rotor wind turbine under atmospheric boundary layers - Heming Bai; Nina Wang; Decheng Wan (Ocean Engineering, 2023)

Influence of spatial resolution of PM2.5 concentrations and population on health impact assessment from 2010 to 2020 in China - Heming Bai; Huiqun Wu; Wenkang Gao; Shuai Wang; Yang Cao (Environmental Pollution, 2023)

Double-Edged Mossy Cells in Temporal Lobe Epilepsy: Evil in the Early Stage Through a BDNF-Dependent Strengthening Dentate Gyrus Circuit - Heming Cheng; Qiuwen Lou; Yi Wang; Zhong Chen (Neuroscience Bulletin, 2023)

Analysis of iron and steel production paths on the energy demand and carbon emission in China’s iron and steel industry - Qiang Yue; Xicui Chai; Yujie Zhang; Qi Wang; Heming Wang; Feng Zhao; Wei Ji; Yuqi Lu (Environment, Development and Sustainability, 2023)

Cascading impacts of global metal mining on climate change and human health caused by COVID-19 pandemic - Yao Wang; Heming Wang; Peng Wang; Xu Zhang; Zhihe Zhang; Qiumeng Zhong; Fengmei Ma; Qiang Yue; Wei-Qiang Chen; Tao Du; Sai Liang (Resources, Conservation and Recycling, 2023)

Mapping China's copper cycle from 1950–2015: Role of international trade and secondary resources - Min Hao; Linbin Tang; Peng Wang; Heming Wang; Qiao-Chu Wang; Tao Dai; Wei-Qiang Chen (Resources, Conservation and Recycling, 2023)

Total CO2 emissions associated with buildings in 266 Chinese cities: characteristics and influencing factors - Yao Wang; Jing Guo; Qiang Yue; Wei-Qiang Chen; Tao Du; Heming Wang (Resources, Conservation and Recycling, 2023)

Analysis of iron in-use stocks: Evidence from the provincial and municipal levels in China - Qiang Yue; Xicui Chai; Feng Zhao; Junhao He; Yun Li; Heming Wang (Resources Policy, 2023)

Recyclable molten-salt-assisted synthesis of N-doped porous carbon nanosheets from coal tar pitch for high performance sodium batteries - Shiwei Wei; Xiaoyang Deng; Wei Li; Kai Liu; Jianxing Wang; Heming Zhao; Xiaoguang Wang (Chemical Engineering Journal, 2023)

What Iodine Intervention Measures Should Be Taken in Different Water Iodine Areas? Evidence from a Cross-sectional Chinese Survey - Yang Du; Peng Liu; Fangang Meng; Lijun Fan; Qingzhen Jia; Weidong Li; Wen Jiang; Jing Ma; Heming Zheng; Peihua Wang; Dianjun Sun; Hongmei Shen (Biological Trace Element Research, 2022)

Co‐benefits analysis of industrial symbiosis in China's key industries: Case of steel, cement, and power industries - Qi Zhang; Ting Xiang; Wei Zhang; Heming Wang; Jing An; Xiuping Li; Bing Xue (Journal of Industrial Ecology, 2022)
Accelerating the construction of ecological civilization in the industrial field and guiding the transformation of industry toward a green direction have become a national development strategy. Promoting the coordinated development of energy‐intensive industries such as steel, cement, and power is a key breakthrough in achieving the green transformation of various industries. This study has designed a steel–cement–power polygeneration system with the collaborative utilization of solid waste resources as the ecological link point. Four scenarios, including business‐as‐usual, optimization of product structure, low‐carbon technology application, and policy advancement (PAD), were established to assess the overall energy‐saving and emissions reduction potential of the steel–cement–power polygeneration system from 2015 to 2050. The results show that product structure adjustment and industrial symbiosis have a significant impact on energy saving and emission reduction of key industries. In 2050, the total energy consumption and carbon emissions of the polygeneration system could reach 38,697.64 PJ and 3766.73 Mt CO 2 . Based on the scenario analysis, the production and use of solid waste in the polygeneration system and the economic benefits are also discussed. Under the PAD scenario, by 2050, the proportion of fly ash as cement raw material will increase to 41%, while the supply of blast furnace slag may be insufficient, and the comprehensive utilization of solid waste can bring economic benefits of 238.32 billion Yuan to the system.

Materials footprint of household consumption in China - Jingru Liu; Haotong Wu; Xin Tian; Heming Wang; Yinglei Wu (Journal of Industrial Ecology, 2022)
China has been witnessing profound changes in the consumption behaviors of its population during the last several decades. To better gauge the current consumption structure of Chinese households and investigate the burden exerted by consumption on resources, we calculated the household material footprint (HMF) in China within the individual consumption classification framework developed by the United Nations. HMF is the only life‐cycle‐based indicator adopted into the 2030 Agenda for Sustainable Development. Four types of raw materials and 15 representative consumption divisions were analyzed in this research. The total HMF in China increased by 103% from 1992 to 2017, although the per capita HMF remains lower than the global average. The per capita HMF growth in rural and urban areas differs, with urban citizens consuming 2.8 more metric tons of resources than rural residents as of 2017. The HMF of all materials studied shows a rising trend, especially for metal ores, which underpins the real estate and auto industries. Food‐related consumption is the main contributor to the HMF in China, while consumption of housing and transportation has less proportion yet more growth potential compared with developed countries. This study adds to the literature of studies on the consumption behaviors and domestic demands of China and has further methodologically significant meaning for similar studies in other countries and practical value for policymakers. Overall, this study demonstrates that despite an upsurge in consumption behaviors and gratifying economic records, the incurred resource and environmental burden may fuel risks for sustainable development.

Transformation Behavior of Iron Minerals in High-Iron Red Mud During High-Pressure Hydrothermal Reduction - Heming Wang; Yiyong Wang; Hui Jin; Jidong Li; Xiaomin Wang (Bulletin of Environmental Contamination and Toxicology, 2022)

Spatiotemporal dynamics and influencing factors of the global material footprint - Heming Wang; Yao Wei; Yueming Wu; Xinzhe Wang; Yao Wang; Guoqiang Wang; Qiang Yue (Environmental Science and Pollution Research, 2022)

Revealing the Precise Role of Calretinin Neurons in Epilepsy: We Are on the Way - Yingbei Qi; Heming Cheng; Yi Wang; Zhong Chen (Neuroscience Bulletin, 2022)

Urban development and sustainability challenges chronicled by a century of construction material flows and stocks in Tiexi, China - Jing Guo; Tomer Fishman; Yao Wang; Alessio Miatto; Wendy Wuyts; Licheng Zheng; Heming Wang; Hiroki Tanikawa (Journal of Industrial Ecology, 2021)

Bone Mineral Density in Population Long-Term Exposed to Rare Earth Elements from a Mining Area of China - Heming Liu; Haiyan Liu; Zenghua Yang; Kunzheng Wang (Biological Trace Element Research, 2021)

CO 2 emissions from the Chinese cement sector: Analysis from both the supply and demand sides - Tao Du; Jian Wang; Heming Wang; Xin Tian; Qiang Yue; Hiroki Tanikawa (Journal of Industrial Ecology, 2020)
China is the largest producer and consumer of cement worldwide, and cement production entails the release of substantial carbon dioxide (CO 2 ) emissions. As the cement sector is a crucial sector of the Chinese economy, understanding the role of supply‐ and demand‐side factors may help accelerate efforts to mitigate CO 2 emissions. However, few studies have analyzed the critical factors affecting CO 2 emissions in the sector based on a combined supply‐ and demand‐side perspective. In this study, we developed an integrated framework that included eleven indicators covering both the supply and demand sides. Results revealed that improving cement production technology cannot offset CO 2 emissions from the growth in demand for cement. Improving technology on the supply side would considerably reduce CO 2 emissions from Chinese cement production; nevertheless, the combination of rapid urbanization, GDP growth, and an ultra‐high fixed capital formation ratio on the demand side increased CO 2 emissions nearly 25‐fold from 1990 to 2015. Notably, some demand‐side factors also had an effect that reduced CO 2 emissions. The in‐use stock per unit of fixed capital formation and output per in‐use stock reduced CO 2 emissions by 332 million metric tons, which is comparable to the contribution of technological progress. Based on these results, we examine why these demand‐side factors substantially influence CO 2 emissions in the Chinese cement sector, and we provide recommendations for policy‐makers on carbon‐reduction measures in this CO 2 ‐intensive sector.

Preparation of heterogeneous Fenton catalyst γ-Cu-Ce-Al2O3 and the evaluation on degradation of phenol - Mei Li; Xinyu Gao; Heming Liu; Hongbo Wang; Qian Zhao; Ning Wang (Environmental Science and Pollution Research, 2020)

Regional material flow accounts for China: Examining China's natural resource use at the provincial and national level - Heming Wang; Heinz Schandl; Guoqiang Wang; Lin Ma; Yao Wang (Journal of Industrial Ecology, 2019)
Over the last three decades, China has experienced the most dynamic economic development lifting living standards and resulting in fast‐growing use of natural resources. In the past, the focus has been on national MFA accounts which do not do justice to the second largest economy, home to 19% of the world population and having 30% of global material use. In this research, we calculate material extraction for China at the regional level during 1995–2015 using the most recent available statistical data and applying the most up‐to‐date international calculation methods. In particular, we combine a bottom‐up and top‐down approach for constructing the dataset of China's economically used Domestic Extraction (DEU) in an integrated way. This approach also improves the Chinese national material flow accounts and allows us to present a reliable database of DE of materials for China to date. Our new dataset provides the basis for calculating material footprints and environmental impacts of China's regions. The dataset enables us to evaluate regional resource efficiency trends in China. We find that during the past two decades, China's material use has grown strongly from 11.7 billion tonnes in 1995 to 35.4 billion tonnes in 2015. Material use has accelerated between 2000 and 2010 but slowed down between 2010 and 2015 reflecting the economic contraction caused by the Global Financial Crisis which reduced the global demand for China's manufacturing and a reorientation of China's economic policy settings toward quality of growth. Unsurprisingly, different regions play different roles in the supply chain of materials, achieving different economic performances resulting in very diverse material efficiency outcomes. This information is important to allow for a targeted policy approach to increase resource efficiency, reduce environmental impacts of resource use, and grow wellbeing in China with large positive implications for global sustainability. This study provides the basis for the development of relevant resource management policies for different regions in the future.

Species with moderate intraspecific trait variability are locally abundant within an environmentally heterogeneous subtropical forest - Guochun Shen; En-Rong Yan; Avi Bar-Massada; Jian Zhang; Heming Liu; Xihua Wang; Mingshan Xu (Oecologia, 2019)

Microbial transformation of resveratrol by endophyte Streptomyces sp. A12 isolated from Polygonum cuspidatum - Tian Jiewei; Wang Lei; Long Xiufeng; Zhang Heming; Li Xiaoguang; Fu Haiyan; Tian Yongqiang (Natural Product Research, 2018)

Iodine Status of Vulnerable Populations in Henan Province of China 2013–2014 After the Implementation of the New Iodized Salt Standard - Jin Yang; Lin Zhu; Xiaofeng Li; Heming Zheng; Zhe Wang; Yang Liu; Zongyu Hao (Biological Trace Element Research, 2016)

Inhibiting cyprinid herpesvirus-3 replication with CRISPR/Cas9 - Yicheng Zhao; Tiedong Wang; Ze Yu; Heming Wang; Bo Liu; Chunyan Wu; Chun-Bo Teng (Biotechnology Letters, 2016)

Decoupling Analysis of the Environmental Mountain—with Case Studies from China - Zhongwu Lu; Heming Wang; Qiang Yue (Journal of Industrial Ecology, 2015)
Summary The resource‐development trajectory of developed countries after the Industrial Revolution of the eighteenth and nineteenth centuries can be portrayed as an “ environmental mountain ” (EM). It is important for developing countries to decouple their resource use from economic growth and tunnel through the EM. In this study, we embedded the decoupling indicators for resource use and waste emissions into EM curves to quantify China's progress in tunneling through the EM over a specific time period. Five case studies regarding the conditions required for decoupling energy consumption, crude steel production, cement production, CO 2 emissions, and SO 2 emissions from economic growth in China were conducted. The results indicated that during 1985–2010 the trajectories of energy consumption, and CO 2 and SO 2 emissions in China met the requirements for tunneling through the EM, but the trajectories of cement and steel production did not. Based on these results, suggestions regarding China's environmental policies are provided to enable the country to tunnel through the EM.

Serum Proteomic Analysis Based on iTRAQ in Miners Exposed to Soil Containing Rare Earth Elements - Heming Liu; Jianzhong Wang; Zenghua Yang; Kunzheng Wang (Biological Trace Element Research, 2015)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)

Decoupling Analysis of Four Selected Countries - Heming Wang; Seiji Hashimoto; Qiang Yue; Yuichi Moriguchi; Zhongwu Lu (Journal of Industrial Ecology, 2013)
Summary We examine decoupling conditions of domestic extraction of materials, energy use, and sulfur dioxide (SO 2 ) emissions from gross domestic product (GDP) for two BRIC (Brazil, Russia, India and China) countries (i.e., China and Russia) and two Organisation for Economic Co‐operation and Development (OECD) countries (Japan and the United States) during 2000–2007, using a pair of decoupling indicators for resource use ( D r ) and waste emissions ( D e ) and the decoupling chart, which can distinguish between absolute decoupling, relative decoupling, and non‐decoupling. We find that (1) during 2000–2007, decoupling between environmental indicators and GDP was higher in the two OECD countries as compared with the two BRIC countries. The key reason is that these countries were in different development stages with different economic growth rates. (2) Changes in environmental policies can significantly influence the degree of decoupling in a country. (3) China, Japan, and the United States were more successful in decoupling SO 2 emissions from GDP than in decoupling material and energy use from GDP. The main reason is that, unlike resource use, waste emissions (e.g., SO 2 emissions) can be reduced by effective end‐of‐pipe treatment. (4) The decoupling indicator is different from the changing rate of resource use and waste emissions. If two countries have different GDP growth rates, even though they may have similar values using the decoupling indicator, they may show different rates of change for resource use and waste emissions.

Resource Use in Growing China - Heming Wang; Seiji Hashimoto; Yuichi Moriguchi; Qiang Yue; Zhongwu Lu (Journal of Industrial Ecology, 2012)
Summary Natural resources provide the basis for our life on Earth. This article presents the accounts of China's direct material input (DMI) during 1998–2008. Using decomposition, we examine factors that have influenced changes in recent resource use in China. China's resource demand in 2011–2015 is projected, based on China's 12th Five‐Year Plan. Finally, effective policies to restrain China's resource demand are discussed with the following conclusions: (1) During 1998–2008, China's DMI doubled, from 11 gigatons (Gt) to 22 Gt. Metallic minerals had the strongest growth, quadrupling; nonmetallic minerals and fossil fuels more than doubled, but biomass remained stable. In relative terms, nonmetallic minerals dominated, with more than 60% of total DMI. (2) Factors of affluence ( A ) and material use intensity ( T ), respectively, contributed most to the increase and decrease of DMI, but the overall decrease effect is much smaller. Factors of population ( P ) and recycling ( R ) only slightly affected changes in China's DMI. (3) During 2008–2015, China's DMI is expected to increase by 27% to 38%, from 22 Gt to 28 to 31 Gt. The average annual rate of increase of DMI would drop to 3% to 5%, from 7% during 1998–2008. (4) Designing new products and infrastructure that use less energy and materials and changing consumption patterns to be more sustainable are crucial to the future resource strategy of China. More policies are expected to improve China's material use intensity and recycling levels.